Teaching mathematics through cultural contexts and motivation: A study on coastal students’ numeracy learning in West Papua - Harlina Harni; Hartono; Yustitia, Via (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study explores the effect of culturally responsive teaching (CRT) and learning motivation on numeracy achievement among elementary students in coastal West Papua, Indonesia. It investigates how integrating local cultural contexts into mathematics instruction and fostering student motivation can enhance learning outcomes. Method: A quantitative ex post facto design was applied, involving 30 third-grade students from SD Negeri 35 Kimindores. Data were gathered through a culturally responsive teaching scale, a learning motivation questionnaire, and a contextual numeracy test. Multiple regression analysis was used to assess the relationship between these factors. Finding: The analysis revealed that both culturally responsive teaching and learning motivation significantly impacted numeracy achievement, explaining 69% of the variance in students' performance. Students exposed to culturally relevant lessons showed greater motivation and improved numeracy skills. Significance: The study highlights the value of culturally responsive pedagogy in improving student engagement and achievement in mathematics. By aligning lessons with students' cultural contexts, educators can make learning more meaningful and inclusive. This research emphasizes the need for culturally grounded teaching strategies, particularly in remote areas, to ensure educational equity and foster deeper learning.